1999
DOI: 10.1111/j.1532-5415.1999.tb01894.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin‐6 and Other Biologic Variables with Depression in Older People Living in the Community

Abstract: These data suggest that the inflammatory marker, IL-6, is associated with depression in older people in this cross-sectional study. These results are compatible with the hypothesis of cytokine (IL-6) stimulation in geriatric depression as part of an overall immunoendocrine dysregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
165
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(173 citation statements)
references
References 34 publications
(56 reference statements)
4
165
3
1
Order By: Relevance
“…Both depression and type 2 diabetes are found to be associated with increased Creactive protein, TNF-α and proinflammatory cytokines, including IL-6 [38][39][40][41][42]. A contradiction between this hypothesis and the first hypothesis is that cortisol inhibits inflammation and the immune response, whereas depression is associated with both elevated cortisol and increased inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Both depression and type 2 diabetes are found to be associated with increased Creactive protein, TNF-α and proinflammatory cytokines, including IL-6 [38][39][40][41][42]. A contradiction between this hypothesis and the first hypothesis is that cortisol inhibits inflammation and the immune response, whereas depression is associated with both elevated cortisol and increased inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…(Dentino et al, 1999;Penninx et al, 2003;Tiemeier et al, 2003;Ford, Erlinger, 2004;Liukkonen et al, 2006;Cyranowski et al, 2007;Dantzer, Kelley, 2007;Ranjit et al, 2007;Bremmer et al, 2008) The cognitive symptoms of depression can be considered an indicator of early stages of clinically diagnosed depression. (Fogel et al, 2006) Thus, our results suggest that inflammation plays a role as an initiator and contributor to the progression of depression rather than contributing to the later stages of depression development.…”
Section: Inflammation As a Predictor Of Depressive Symptomsmentioning
confidence: 99%
“…(Danesh et al, 2004) Both experimental and epidemiological research have found that depressed people have higher plasma levels of inflammatory markers. (Dentino et al, 1999;Penninx et al, 2003;Tiemeier et al, 2003;Ford, Erlinger, 2004;Liukkonen et al, 2006;Cyranowski et al, 2007;Dantzer, Kelley, 2007;Ranjit et al, 2007;Bremmer et al, 2008) However, experimental research is based on small clinical samples, and previous epidemiological research, despite large samples and thorough covariate assessment, is cross-sectional. Generally these studies have examined short-term associations between depression and inflammation, while examination of longer term associations is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is proposed to be involved in the pathophysiology of MDD. In particular, it was suggested that IL-6 is involved in multiple physiological systems, including the hypothalamic-pituitary-adrenal axis, corticotrophin-releasing hormone activity at limbic sites, noradrenaline utilization, the release of oxidative stress, apoptotic pathways, and kinase signaling, all of which have very close relationships to the pathophysiology of MDD [13][14][15]. Li et al recently showed that noradrenaline significantly increased the mRNA and protein expressions of IL-6 in U937 macrophages in time-and concentration-dependent manners [16].…”
Section: Discussionmentioning
confidence: 99%